PERAN HUMAS DALAM PENGEMBANGAN PENDIDIKAN PADA ERA OTONOMI - aan an widianto (VICRATINA, 2018)
Organizationnis currently experiencing growth and remarkable development. An increasinglyydiverse public characters, both interal and external, require special handling in communicating to them. Communication activities of the organization is a strategic communications activities that need to be run by the organization. This communicationnactivities involving management as important decision makers in the organization. Through public relations activities of the organization’s strategic communication can run well. Public relations must have the full support of management to be able to carry out the task.